Recent advances in the determination of G protein-coupled receptor structures. (August 2018) - Thal, David M; Vuckovic, Ziva; Draper-Joyce, Christopher J; Liang, Yi-Lynn; Glukhova, Alisa; Christopoulos, Arthur; Sexton, Patrick M
Highlights: Recent technological advances in GPCR structural biology have led to many new and exciting structures. Protein engineering remains important for determining new structures. Advances in XFEL and synchrotron technology offer new methods for data collection. Multiple active-state GPCR-G protein bound structures have been determined by cryo-EM. Abstract : G protein-coupled receptors (GPCRs) are the largest superfamily of cell surface receptor proteins and are important drug targets for many human diseases. In the last decade, remarkable progress has been made in the determination of atomic structures of GPCRs with over 200 structures from 53 unique receptors having been solved. Technological advances in protein engineering and X-ray crystallography have driven much of the progress to date. However, recent advances in cryo-electron microscopy have facilitated the structural determination of three new structures of active-state GPCRs in complex with heterotrimeric G protein. These advances have led to significant breakthroughs in our understanding of GPCR biology including not only how signal transducers such as G proteins or arrestins interact with receptors, but also pave the way for future structure-based drug design.